The Effect of Work Environment and Motivation on Job Satisfaction - Pujiarti Pujiarti; Heri Satrianto Satrianto; Tri Angreni Angreni (eCo-Fin, 2019)
The formulation of this problem is the work environment and motivation. Towards job satisfaction The research model used is a descriptive research model which describes systematically and accurately the factors studied. The data testing technique used in this study includes a validity test with a calculated r value and a reliability test with a Cronbach's Alpha value, the data analysis used is multiple linear regression to test and prove the research hypothesis. The research method carried out by the author is in the form of data collection, processing data, analyzing data and presenting data so that the results presented by this author are scientific and accountable. By using correlation coefficient analysis, it is known that the influence of work environment and motivation on job satisfaction. The regression coefficient of the work environment variable (b1) is 0.521. This means that if the value of X1 (work environment) has increased by 1 unit, assuming the other dependent variables are fixed, then the level of variable Y (Job Satisfaction) will increase by 0.521. and every increase or decrease in motivation by 1 point, then the job satisfaction of employees at PT. Relazindo Usaha Bersama will increase or decrease by 0.403. And vice versa if the value of X1 decreases, while the variable X2 remains, the level of variable Y will decrease. From the results of multiple linear regression analysis Y = 13,532 + 0.521 X1 + 0.173 X2, meaning that every increase or decrease in the Work Environment by 1 point, then the job satisfaction of employees at will increase or decrease by Based on the results of hypothesis testing, it is obtained that F count to determine the Work Environment and Motivation is 0.000 and 0.000 or the probability is below 0.05 then it meets the criteria which means Ho is rejected and Ha is accepted or the regression coefficient is significant or Work Environment and Motivation has a significant effect on job satisfaction. From the results of the F test, model 1 obtained a value of 181,711 and model 2 obtained a value of 100,757 where the value is greater than the F table of 3.09, then H0 is rejected and Ha is accepted. From the results of the t test, the t count of the work environment is 7.555, and the t count of motivation is 2.755, where the value is greater than the t table of 1.66055, then H0 is rejected and Ha is accepted, meaning that there is a significant relationship between the work environment and motivation towards job satisfaction